Pendampingan Pengelolaan Keuangan dan Strategi Pemasaran Digital untuk Meningkatkan Daya Saing Tenun Ndao: Financial Management Assistance and Digital Marketing Strategies to Improve the Competitiveness of Ndao Weaving - Siprianus G. Tefa; Dominikus Kopong Toni Aman; Melianus E. Tkela (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This Community Empowerment Partnership aims to improve the competitiveness of Ndao woven products through financial management assistance and digital marketing strategies in Mbali Lendeiki Village, Ndao Nuse District, Rote Ndao Regency, home to 26 weavers, all of whom are housewives. The challenges faced by the group include limited working capital for expanding the weaving business, low financial literacy, and conventional marketing practices for weaving. To address these issues, the team, with grant funding from the Ministry of Education, Culture, Research, and Technology, implemented an integrated and participatory approach through four main strategies: providing raw materials for weaving production, conducting outreach and training, providing bookkeeping assistance using Microsoft Excel, and creating Shopee e-commerce accounts for Ndao weavers. The evaluation results of the PKM implementation showed that 80.8% of weaving members found the financial training beneficial, and 73.1% considered digital marketing relevant. However, only 26.9% of weaving members were willing to implement bookkeeping, and 34.6% were ready to sell weaving products digitally. The findings from this PKM indicate the need for ongoing mentoring to enhance the Ndao weaving group's competitiveness.